Community preparedness towards major accident events in Gebeng Industrial Area, Kuantan - Marliza, Ismail (2018)
This thesis deals with community preparedness towards major accident events that may occur at Taman Balok Perdana, Kuantan. The main objective of this thesis was to utilize the result of the study in order to improve the community preparedness towards the major accident events. Furthermore, the first objective is to measure the level of community awareness and knowledge towards major accident hazards. The first objective was completed by using questionnaire. From those sources it was identified that the community had high and moderate awareness and knowledge regarding it. The method used was walkthrough observation, semi-structured interview in focus group discussion and document review for the second and third objective was achieved which is to identify the existing practices of community organization towards the emergency preparedness and to identify the decision process made by the community leader during emergency response on major accident events. However, there is no specific practices that been done related to major accident events and the decision process from the community leader only and they was depending on local authority for further action. In order to increase the preparedness of the community,some recommendation had been proposed such as by doing awareness campaign, increase the involvement of stakeholder and community, preparing a contingency plan, and developt a community based disaster risk management (CBDRM). Therefore, the outcome of the study can be used by responsible stakeholder in order to improve more on community preparedness.